2000
DOI: 10.1007/s005200050287
|View full text |Cite
|
Sign up to set email alerts
|

Oral sequelae of chemotherapy: an important teaching opportunity for oncology health care providers and their patients

Abstract: The object of this work was to conduct a rapid assessment of a teaching hospital's promotion of optimal oral health among its chemotherapy patients. A pilot study was undertaken, which included focus interviews with oncology clinic staff, a review of the fellowship training curriculum, and unobtrusive observations in the clinic setting. Charts were also audited for oncology patients who were probable chemotherapy candidates. A review of the data offered no evidence that oral health care was routinely addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It remains unclear whether the less satisfied patients did not receive sufficient information or the patients lost information, due limited capacity and the enormous amout of information as Sadler et al showed previously [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether the less satisfied patients did not receive sufficient information or the patients lost information, due limited capacity and the enormous amout of information as Sadler et al showed previously [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have noted the relative lack of oral care information in the curricula of professional schools [8,9,21,22] and even expressed concern about whether clinical educators are serving as adequate role models for students [28]. Clearly, there is a need for better basic and continuing education following initial professional preparation [1,14].…”
Section: Gaps In Knowledgementioning
confidence: 99%
“…Lastly, it is increasingly evident in clinical practice that patients and their families also have significant gaps in knowledge about oral complications of cancer and how to manage them [12,18,20,28]. Effective patient educational material appears to be lacking [35] and a focus on comprehensive education of patients and their families is warranted [8,9].…”
Section: Gaps In Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Newly diagnosed patients are estimated to retain less than 20% of the information that is given to them [14]; therefore, it is essential to develop strategies that help them remember more than 20% of the information provided. In general, people remember 20% of what they hear, 30% of what they see, 50% of what they hear AND see, 70% of what they hear, see, and say, and 90% of what they hear, see, say, and do [2].…”
Section: Strategies To Enhance Education Of Patientsmentioning
confidence: 99%